1989
DOI: 10.1007/bf01506527
|View full text |Cite
|
Sign up to set email alerts
|

Studies of jet production rates ine + e ? annihilation atE cm=29 GeV

Abstract: Production rates of multijet hadronic final states are studied in e § -annihilation at 29 GeV center of mass energy. QCD shower model calculations with exact first order matrix element weighting at the first gluon vertex are capable of reproducing

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

1989
1989
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(5 citation statements)
references
References 21 publications
2
3
0
Order By: Relevance
“…The data were compared with the leading-logarithmic-approximation (LLA) model . Similar studies based on the MARK II data at PEP ( √ s = 29 GeV) are found in [173] and [174] using the so-called "optimised perturbation theory", i.e., by fitting the scale. An earlier attempt to establish the non-abelian nature of QCD from a study of multijet events was made by the AMY collaboration at the TRISTAN e + e − storage ring at the KEK laboratory [175].…”
Section: Quantitative Studies Of Qcd At Petra and Pepsupporting
confidence: 68%
See 1 more Smart Citation
“…The data were compared with the leading-logarithmic-approximation (LLA) model . Similar studies based on the MARK II data at PEP ( √ s = 29 GeV) are found in [173] and [174] using the so-called "optimised perturbation theory", i.e., by fitting the scale. An earlier attempt to establish the non-abelian nature of QCD from a study of multijet events was made by the AMY collaboration at the TRISTAN e + e − storage ring at the KEK laboratory [175].…”
Section: Quantitative Studies Of Qcd At Petra and Pepsupporting
confidence: 68%
“…The data were compared with the leading-logarithmic-approximation (LLA) model . Similar studies based on the MARK II data at PEP ( √ s = 29 GeV) are found in [173] and [174] using the so-called "optimised perturbation theory", i.e., by fitting the scale.…”
Section: Quantitative Studies Of Qcd At Petra and Pepsupporting
confidence: 68%
“…Then there will be roughly 4 × 10 4 four jet events with two tagged b-quarks (using the JADE scheme with y cut = 0.01, as in figs. [3][4][5][6]. This is an order of magnitude less than the total number of four jet events, but in return we gain greater power to discriminate between the various terms in the four jet cross section, particularly between the Abelian, QED-like term and the non-Abelian term in the two quark, two gluon cross section.…”
Section: Discussionmentioning
confidence: 99%
“…Important results have been achieved. The strong coupling constant α s has been determined from jet rates and from shape variables [2] and both the flavour independence [3] and the running with √ s [4] have been verified. Three- [5] and four-jet [6] distributions have been studied and their behaviour agrees with QCD predictions calculated to second order in α s .…”
Section: Introductionmentioning
confidence: 95%
“…We proceed by collecting various measurements spanning PETRA, PEP, TRIS-TAN, LEP 102,103,52,104,105,106,107], and in our case, SLC. These measurements represent energies Vs=22-92 GeV in ee-machines.…”
Section: Running Of Amentioning
confidence: 99%